Predicting entrepreneurial intention and economic development: A cross-national study of its policy implications for six ASEAN economies - Thanaphol Virasa; Krisakorn Sukavejworakit; Triyuth Promsiri (Heliyon, 2022)
In this study, entrepreneurial intentions (EI) among individuals in six ASEAN (Association of Southeast Asian Nations) countries (Vietnam, the Philippines, Indonesia, Thailand, Malaysia, and Singapore) were investigated by applying the theory of planned behavior (TPB) to understand the underlying predictors of EI among three different stages of economic development. To investigate the predictors of EI according to TPB, the datasets of 13,358 respondents from the Global Entrepreneurship Monitor (GEM) national teams were analyzed using a binary logistic regression (BLR) model for each country, which was then grouped concerning the status of national economic development to compare the differences. The GEM datasets showed that attitude towards behavior (ATB) was highest in the Philippines (ATB1 = 81.8, ATB2 = 78.1), the subjective norm (SN) was highest in Vietnam (SN1 = 86.8), and Indonesia (SN2 = 69.2), the perceived behavioral control (PBC) was highest in the Philippines (PBC1 = 66.2) and Thailand (PBC2 = 47.3), which predicted that the Philippines, Indonesia, Thailand, and Vietnam have the highest EI amongst this group of six ASEAN nations. Furthermore, the analysis used multi-variables to predict EI, showing that the predictors influencing EI in factor-driven economies (Vietnam and Philippines) are only subjective norms (SNs) and PBC. However, predictors which influence the EI in efficiency-driven economies (Indonesia, Thailand, and Malaysia) and innovation-driven economies (Singapore) are ATB and SNs. The results strongly support that PBC can be the best predictor of EI for ASEAN adult populations (ages 18–64). These findings potentially give government and private sectors an advantage in policy management for new business creation concerning each stage of economic development for each respective nation.